2005
DOI: 10.1080/15438620590956197
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effect Of Proprioceptive and Balance Exercises on People With an Injured Or Reconstructed Anterior Cruciate Ligament

Abstract: This systematic review investigated the effect of proprioceptive and balance exercise on outcomes following injury and surgical reconstruction of the anterior cruciate ligament (ACL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 17 publications
1
39
0
5
Order By: Relevance
“…However, Jennings and Seedhom [49] recruited participants who had undergone arthroscopy sometime in the previous 10 years without reporting if the participants in the ACL-deficient knee group had undergone any proprioceptive training, while Beard et al [48] recruited participants within 18 months of arthroscopy and none of their participants had received any proprioceptive training. This difference in participant populations may have resulted in the disparity in the results obtained from these two studies, as sensorimotor training may enhance neural drive and subsequently improve joint proprioception [50][51][52], thereby reducing the delayed onset of the ACL-hamstring reflex. Friemert et al [53] reported that 10 out of 10 trials (100%) elicited stretch reflex during an intraoperative direct mechanical stimulation of the anterior cruciate ligament.…”
Section: Afferent Feedbackmentioning
confidence: 57%
“…However, Jennings and Seedhom [49] recruited participants who had undergone arthroscopy sometime in the previous 10 years without reporting if the participants in the ACL-deficient knee group had undergone any proprioceptive training, while Beard et al [48] recruited participants within 18 months of arthroscopy and none of their participants had received any proprioceptive training. This difference in participant populations may have resulted in the disparity in the results obtained from these two studies, as sensorimotor training may enhance neural drive and subsequently improve joint proprioception [50][51][52], thereby reducing the delayed onset of the ACL-hamstring reflex. Friemert et al [53] reported that 10 out of 10 trials (100%) elicited stretch reflex during an intraoperative direct mechanical stimulation of the anterior cruciate ligament.…”
Section: Afferent Feedbackmentioning
confidence: 57%
“…[41][42][43][44][45][46][47] Alternatif yaklaşımlardan kuru iğneleme ve akupunkturun ağrıyı azaltmada kullanılabileceği konusunda pek çok çalışma vardır. 48,49 Çalışmaya katılan fzt'lerin bu yöntemleri seçim yüzdeleri çok yüksek olmamakla birlikte, %12,9'u kuru iğneleme, %3,2'si akupunktur uygulamasını tercih etmiştir.…”
Section: Bulgularunclassified
“…Soğuk uygulama-kompresyon ve elektrik stimü-lasyonu ile ağrı ve inflamasyon baskılanmakta-dır. 6,7 İyileşmekte olan dokuda inflamatuar yanıtın yeniden başlamaması için; ekleme fazla yüklen-mekten kaçınılmalıdır. Ekleme binen yükü azaltmada çeşitli tesbit yöntemleri ve koltuk değneği kullanımı önerilmektedir.…”
unclassified
“…101 A Cochrane review of exercise therapy after isolated ACL injuries and 2 systematic reviews of ACL rehabilitation identified only 8 studies that evaluated different aspects of nonoperative management. 24,89 None of the 8 studies included rehabilitation of skeletally immature individuals, and no RCTs of different rehabilitation programs for skeletally immature patients with ACL injuries have been published to our knowledge.…”
Section: Physeal Sparing Reconstructionmentioning
confidence: 99%